2021
DOI: 10.1177/08850666211021745
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Secondary Bacterial Infections and Antibiotic Use in Mechanically Ventilated Patients With COVID-19 Induced Acute Respiratory Distress Syndrome

Abstract: Background: COVID-19 has a widely variable clinical syndrome that is difficult to distinguish from bacterial sepsis, leading to high rates of antibiotic use. Early studies indicate low rates of secondary bacterial infections (SBIs) but have included heterogeneous patient populations. Here, we catalogue all SBIs and antibiotic prescription practices in a population of mechanically ventilated patients with COVID-19 induced acute respiratory distress syndrome (ARDS). Methods: This was a retrospective cohort study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 26 publications
2
17
0
4
Order By: Relevance
“…In our study, 53% of patients undergoing early intubation (0-3 days after hospitalization) developed secondary infection. This is in line with findings that mechanically ventilated COVID-19 patients are at high risk of developing secondary infection ( Risa et al., 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, 53% of patients undergoing early intubation (0-3 days after hospitalization) developed secondary infection. This is in line with findings that mechanically ventilated COVID-19 patients are at high risk of developing secondary infection ( Risa et al., 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…COVID-19 has been spreading worldwide with unprecedented rapidity. The disease potentially induces various complications, of which secondary bacterial infections should be regarded as the most harmful events [ 1 ]. Among various bacterial etiologies, recent literature indicated S. aureus -associated infections to be of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature investigated the incidence of secondary bacterial infections in COVID-19 patients with mechanical ventilation due to acute respiratory distress syndrome [ 1 ]. Among 126 cases, 61% developed bacterial infections such as ventilator-associated pneumonia (VAP), blood stream infections, and urinary tract infections in its order, in which Staphylococcus aureus was the most common pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…Most cases of VABP in their study were caused by A. baumannii [ 42 ]. In a retrospective, multicenter study of 126 critically ill patients with COVID-19, of whom 77/126 had positive respiratory cultures (61%), Risa et al [ 19 ] observed 6/77 cases of S. aureus respiratory infection, of which 6 were caused MRSA. In a retrospective study of 178 critically ill patients with COVID-19 for a total of 230 lower respiratory tract specimens, there were 15/230 lower respiratory tract cultures positive for S. aureus (7%), and 6/15 were MRSA (40%).…”
Section: Studies Reporting On the Epidemiology Of Staphyloc...mentioning
confidence: 99%
“…Overall, methicillin-resistant S. aureus (MRSA) has been reported to cause up to 9% and 23% of CABP and HABP, respectively. However, the exact burden of MRSA lung infection in peculiar populations such as patients with COVID-19 remains somewhat elusive, possibly because of wide heterogeneity in methods and endpoints across studies (with many of them focused on other aspects and reporting only marginally on the epidemiology of causative agents of bacterial co-infection or superinfection), as well as in the approach to etiological diagnosis (e.g., different frequencies of collection of deep respiratory specimens for culture or molecular testing in COVID-19 patients with VABP) [1,2,4,[15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%